Blockchain and information integration: Applications in New Zealand’s prefabrication supply chain - Bakhtiarizadeh E; Shahzad WM; Poshdar M; Khalfan M; Rotimi JOB (MDPI (Basel, Switzerland), 2021)
New Zealand’s rising demand for new and affordable homes is driving innovative and effective methods for project delivery. Prefabrication or off-site construction is considered an innovative approach to project delivery that eliminates the limitations of traditional construction methods. However, the prefabrication industry struggles with several challenges, including poor coordination and low supply chain integration amongst its partner organisations. There has been previous literature on improving the prefabrication supply chain integration, but few studies about the role of technology in this sector. Therefore, this article provides intuitions into the applicability and benefits of advanced technologies, namely blockchain, for improving supply chain integration in the context of prefabrication in New Zealand. A questionnaire survey was used to identify the channels used for information exchange between clients and contractors. Moreover, the questionnaire ascertained the positive effects of blockchain on enhancing supply chain integration between the two partners. Blockchain has proven to be a secure information integration instrument that can improve the integration of the prefabrication supply chain by fostering collaboration between organisations.
Keywords: prefabrication; supply chain; communication channels; information integration; blockchain; New Zealand